PERSPEKTIF GENDER PADA MASYARAKAT KOTA BANDA ACEH - Cahayu Astina (Program Pascasarjana IAIN Langsa, 2019)
This study aims to find out the perspective of the people in Banda Aceh regarding gender relations and to find out how the implementation of gender relations in the household life of the community in Banda Aceh City. The theory that forms the basis of this research is Bourdieu's theory which views power in the context of the theory of society, where he sees power as a culture and artificial symbolism which is continually legitimized through agent interaction and structure. The main way this happens is through what is called